Investigating the Role of Unemployment on Relationship Breakdown Among the Unemployed Ghanaian Youth - William, Daitey; Panin Kwame Baah, Owusu; Eddy Mary, Takyi; Selasi, Ahiabu; Emmanuel, Bonsu (Lafadz Jaya Publisher, 2024)
This study examines the relationship between unemployment and relationship breakdown among youth in Ghana. Unemployment among youth has become a pressing issue globally, particularly in developing countries like Ghana. The objective is to investigate how the experience of unemployment influences relationship stability among young adults. The study employs qualitative research methods, including interviews and focus groups to gather data from unemployed youth in various regions of Ghana. Factors such as financial stress, decreased self-esteem, and the strain on interpersonal relationships due to unemployment were some of the perceptions by the unemployed youth in Ghana. The findings aim to contribute to a better understanding of the social impacts of unemployment and provide insights into potential interventions to support youth navigating these challenges in Ghanaian society.